Implementation of Sustainable Tourism in Bekelir Village - Rosianna Sianipar; Nova Bernedeta Sitorus (Jurnal Mantik, 2022)
In order to avoid these negative impacts, the application of tourism experiences a hurdle, namely how to find methods to increase welfare by using natural resources in an efficient manner wisely in order to meet the needs of future generations. Therefore, the implementation of sustainable development is needed to maintain tourist destinations in various aspects. Sustainable development is development that meets the needs of the present and does not reduce its ability to meet the needs of future generations. Sustainable tourism development is all forms or types of development, regulation, and integrated tourism activities to ensure the maintenance of natural and cultural resources that aim to ensure long-term and sustainable prosperity. The purpose of this study is to analyze the implementation of sustainable tourism in Bekelir Village. The type of research that the research team used in this study was qualitative research. Based on the results of research with interview techniques on the Implementation of Sustainable Tourism in Bekelir Tourism Village, the following conclusions can be drawn. Bekelir Tourism Village implements sustainable tourism and its application according to which can be measured through the three indicators proposed by Durovic & Lovrentjev (2014), namely the social, economic, and environmental dimensions. Regarding the social dimension, Bekelir Tourism Village has been conserving its cultural heritage, paying attention to social carrying capacity, and maintaining its local wisdom. Regarding the economic dimension, tourism has a positive influence by presenting tourism products with good quality which can be seen from the economic benefits for local communities, Institutional regulation, Seasonality of tourism activity. Regarding the environmental dimension, Bekelir Tourism Village has considered carrying capacity and reducing pollution from tourism activities which can be seen from the management and protection of the environment as well as waste management.